The outcomes of anatomical lung resection for nontuberculous mycobacterial lung disease - Sakane, Tadashi; Matsuoka, Katsunari; Kumata, Sakiko; Watanabe, Risa; Yamada, Tetsu; Matsuoka, Takahisa; Nagai, Shinjiro; Ueda, Mitsuhiro; Miyamoto, Yoshihiro (Journal of Thoracic Disease, 2018)
Background: The number of cases of nontuberculous mycobacterial (NTM) lung disease has been increasing in recent years, and the efficacy of surgical treatment has been recognized. We investigated the clinical characteristics and behavior of NTM lung disease and analyzed the outcomes of surgery. Methods: The data of 25 patients who underwent anatomical resection for NTM lung disease in our institution between January 2004 and December 2014 were retrospectively examined. Results: The patients included 10 men and 15 women (mean age, 63.1 years). Twenty patients had Mycobacterium avium, and 5 had Mycobacterium intracellular. The indications for lung resection in 20 definitively diagnosed patients included a remaining or worsening lesion despite medical treatment (n=16), massive hemoptysis or bloody sputum (n=5), and prolonged smear positivity (n=1); multiple reasons were allowed. In five cases without a definitive diagnosis, surgery was performed due to the suspicion of lung cancer. The surgical procedures included pneumonectomy, n=4; lobectomy, n=13; and segmentectomy, n=8. Complete resection was achieved in 10 cases (40.0%). Video-assisted thoracoscopic surgery (VATS) was performed in 17 cases (68.0%), especially in 6 of 8 cases (75.0%) that underwent segmentectomy and in 10 of 11 cases (90.9%) that received simple lobectomy. There was one case of hospital mortality. Among the 22 patients who were followed at our institution, relapse occurred in 4 patients, and new infection occurred in 1 patient. NTM lung disease was controlled in 17 patients (77.3%). In the four cases that relapsed, the median relapse-free interval was 29.5 months. Conclusions: Surgical resection was a feasible treatment for NTM lung disease and was associated with favorable outcomes, although there was 1 case of hospital mortality. VATS procedures were considered adequate for the treatment of NTM lung disease; however, the surgical indications must be carefully considered.